PEDAGOGICAL CONDITIONS OF FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE TEACHERS OF PHILOLOGICAL DISCIPLINES IN THE PROCESS OF GENERAL PEDAGOGY (Pedagogy of Higher and Secondary Education, 2010)
The article deals with the professional competence of future teachers of philological subjects as a complex integral systematic personal unit, the pedagogical conditions of its formation are defined.
Keywords: professional competence of future teachers of philological subject; complex integral systematic personal unit; pedagogical conditions of formation of professional competence of future teachers of philological subjects